OPTIMALISASI BIAYA DAN WAKTU PROYEK MENGGUNAKAN METODE CRASHING DENGAN PENAMBAHAN WAKTU KERJA (LEMBUR) DAN SISTEM KERJA SHIFT - Adityawan Sigit (TEKNISIA, 2018)
On every project construction often found problem about delay work project, this happen consequence existence difference condition location project, change design, weather or error in planning project. Consequence from delay work project this happen accretion cost project and project finished through from the planned time. Development Project and Development of Magelang Type B Hospital located on Jl. Raya Magelang -Yogyakarta, Mungkidan, Village Danurejo, District Mertoyudan, Regency Magelang, Central Java is project development and development House sick beforehand. Moment implementation development project experience delay because of factor where the climate the beginning of the implementation process project enter season rainy day. With existence problem that is then will do analysis schedule construction with use PDM method ( Precedence Diagram Method ) on Development Project and Development of Magelang Type B Hospital use method acceleration (crashing) with additions time work ( overtime ) 1 hour, 2 hours, 3 hours and working hours shift . Where aim from analysis that is for knowing the total time and cost project and knowing time acceleration (crashing) efficient and costs economical. From the destination research this obtained results analysis in a manner economical cost acceleration (crashing) with working hours more shift economical with total costs project as big as Rp. 13,881,934,901.31 and for optimal duration time project the fastest that is with acceleration (crashing) additional working hours (overtime) 3 hours with duration time project finished for 154 days or 56% more fast from normal duration is 350 days.